Social Capital that Affects the Forming of Entrepreneurial Intention through Self-Efficacy - Nurhidayani Nurhidayani; Trisno Martono; Dewi Kusuma Wardani (Randwick International of Social Science Journal, 2021)
Understanding the various factors that influence entrepreneurial intentions is very important in efforts to develop entrepreneurship in higher education. Entrepreneurship is currently the center of attention of various parties because it has a contribution to economic development that can be used to overcome the problem of the gap between job opportunities and the available workforce for young people. This study investigates the role of social capital on entrepreneurial intentions and other variables that may mediate the relationship between the two. For this purpose, using a sample of 269 students majoring in education last year at the Sebelas Maret University. Using structured questionnaire in data collection, and tested with SPSS. the results obtained from the collected data indicate that social capital has a direct and indirect influence on entrepreneurial intentions through self-efficacy.